Treatment with perilesional injections of pentoxifylline in patients with Peyronie's disease improves the therapeutic effect of oral and topical antioxidant therapy - Gianni Paulis; Andrea Paulis; Giovanni De Giorgio (Archivio Italiano di Urologia e Andrologia)
To the Editor,